Climate Change Responses - Seebacher, Frank; Post, Eric
Climate Change Responses is an open access interdisciplinary journal dedicated to publishing exceptional research on ecological and evolutionary responses to climate change.  The journal is especially interested in publishing ground-breaking work linking responses to environmental change across levels of biological organization, from individuals to ecosystems, and with an emphasis on species interactions. Articles that establish cause-and-effect relationships rather than correlations between changes in the environment and species responses are particularly welcome. The journal applies a highly selective review process and accepts manuscripts demonstrating novel research covering a broad range of topics, including but not limited to: behavior, ecosystem function and dynamics, evolutionary adaptation and plasticity, paleoecology, phenology, physiology, population dynamics, and broad ecological changes, all within the context of climate change.